Publications and new products (Journal of EAHIL, 2024)
Dear all, welcome back to my column! I hope you all enjoyed this summer and had the chance to rest up and recharge for the upcoming fall. As always, I scanned the web searching news on the most discussed trends related to biomedical librarianship. Once again, it’s Artificial Intelligence (speaking of which, have you read the last JEAHIL issue edited by Michelle Wake on Artificial Intelligence and libraries?), Diamond Open Access and Open Science. Enjoy!